Towards a Phenomenology of the Theatrical Body: Stylistics, Hyperesthesia, and the Suspension of the Lived Body - Fallas Fernández, Daniel (2026)
This article examines the limits that Schiller’s definition of art encounters when confronted with the theatrical phenomenon. The way in which an actor embodies a character on stage constitutes a limit case for Schillerian aesthetics—even if the German thinker remains unaware of it. From this case, the simplifications underlying Schiller’s conception are exposed, in order to then expand his definition of art through a phenomenological perspective and a philosophical anthropology. Specifically, the article draws on the “phenomenology of bodily strata” systematized by the Mexican philosopher Marcela Venebra, with the aim of outlining a phenomenology of the theatrical body. Rather than invalidating Schiller’s ideas, this approach brings them to their highest speculative potential. It concludes that the phenomenological framework is highly productive for philosophically approaching theatrical performance as an aesthetic phenomenon of exceptional singularity.